Numerical Model Analysis of Natural Gas Combustion Burners - Ibraheem, Amjd; Szodrai, Ferenc (International Journal of Engineering and Management Sciences, 2019)
Traditional power plants still the dominating power source for all the major industries and powerdemanding facilities, the most crucial facility for the whole plant operations is the industrial boiler which generatessteam, heating energy or electrical power. Boilers generate energy by combustion. The improvement of combustion efficiency could greatly influence the energy consumption and will make the boiler more efficient and cleaner (less emissions), that’s why it is important to understand the combustion and thermal flow behaviours inside the boiler. Beside experimental testing, computational work nowadays becoming more and more important due to lower cost and acceptable accuracy with minimum error. With numerical calculations method, the computational model created by a Computational Fluid Dynamics (CFD) software could reduce a lot of trial and error on experimental work. In this paper utilizing the ANSYS FLUENT 19.1 software to make crate the combustion model. The ratio of air to fuel mixture, the equivalency factor, mass flow rate of the mixture, velocity, mass fractions of the mixture components (fuel and air) and their temperatures will serve as the input parameter while the exhaust gase component mass fraction, temperature, mass flow and velocity will be monitored.